Governing Sex Work in the City. Issue 8 (August 2014) - Laing, Mary; Cook, Ian R.
Abstract Sex work is often constructed as an urban 'problem'. As a result, sex workers, clients and the spaces in which people buy or sell sex are frequently the subject of intervention from those governing cities. This paper considers the ways in which problems and solutions are framed in the wider governance of sex work in cities in the global north. It draws on a range of academic literature to show how the urban governance of sex work takes relational and territorial forms. Governance is relational in the sense that it is about 'improving' the connections and relationships between those involved in sex work and those seemingly affected by sex work, and it is territorial in that placing sex work in the city through spatial exclusion, containment and the construction and maintenance of spatial boundaries is often the focus of strategies of governance. The paper argues that while the urban governance of sex work is contingent, there are often resonances and connections between cities in how they frame the problem of sex work and the interventions used. The paper concludes by highlighting future areas for research on the subject of sex work, governance and the city.